Monitoring of the Parameters of Intra-Industrial Differentiation of the Primary Industry of the Traditionally Industrial Region of Southern Russia - LITVIN, Dmitriy Borisovich; POPOVA, Svetlana Viktorovna; ZHUKOVA, Viktoriya Artemovna; PUTRENOK, Ekaterina Leonidovna; NAROZHNAYA, Galina Alekseevna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The article set the goal to disclose the profile of competitive advantages of the primary industry of the traditionally industrial region and the structural problems of its development through the development of the specific methodological approach. Results of the study allowed compiling a matrix of static and dynamic differentiation of the industrial sector of the economy and form conceptual and methodological provisions for adjustment of the industrial policy in the region on its base. Results of the study showed that conditions of recession and depression in the industrial sector of the economy have isomorphic nature in various subsectors. Identification of the depth of the gap in the level of their development is an essential condition for balanced growth of the economy of traditionally industrial type. The authors made a search and heuristic attempt to improve the methodological support for monitoring procedures within the management and industry regulation of industrial policy in the system of regional management.